2015
DOI: 10.3354/meps11196
|View full text |Cite
|
Sign up to set email alerts
|

Calcareous spherules produced by intracellular symbiotic bacteria protect the sponge Hemimycale columella from predation better than secondary metabolites

Abstract: Benthic sessile organisms in general, and sponges in particular, have developed an array of defense mechanisms to survive in crowded, resource and/or space-limited environments. Indeed, various defense mechanisms may converge in sponges to accomplish a defensive function in an additive or synergetic way, or to operate at different times during the sponge's life cycle. Moreover, sponges harbor highly diverse microbial communities that contribute in several ways to the host's success. Although some symbiotic bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
10
0
1
Order By: Relevance
“…Conversely, it is generally accepted that for mutualistic symbioses to become evolutionaryly fixed, benefits at the species level should compensate for the costs to the associated partners 41 . The most obvious benefit to sponges from their association with calcifying bacteria is the ‘low cost’ construction of an exoskeleton, which may serve as structural purpose and deter potential sponge predators better than secondary metabolites 42 . Protection against an increase in predators has been proposed as an evolutionary driver of exoskeletons in ancient animals during the Cambrian explosion 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, it is generally accepted that for mutualistic symbioses to become evolutionaryly fixed, benefits at the species level should compensate for the costs to the associated partners 41 . The most obvious benefit to sponges from their association with calcifying bacteria is the ‘low cost’ construction of an exoskeleton, which may serve as structural purpose and deter potential sponge predators better than secondary metabolites 42 . Protection against an increase in predators has been proposed as an evolutionary driver of exoskeletons in ancient animals during the Cambrian explosion 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Siliceous spicules were precipitated and then the pellet was discarded. The spicule-free homogenates were subjected to a series of centrifugations and re-suspensions 42 . One aliquot of the each final spherule suspensions (three per individual) was filtered through 0.2 μm pore filters and filters were CARD-FISH treated ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sponges (phylum Porifera) are considered valuable model systems in host-microbiome research due to the abundance and diversity within their associated microbial communities (Pita, Fraune, & Hentschel, 2016), with a total of 52 bacterial phyla and candidate phyla discovered among sponge hosts (Thomas et al, 2016). Spongemicrobiome interactions are numerous and complex, and microbial symbionts may confer a number of benefits to their host including nutrition and waste metabolism (Freeman, Thacker, Baker, & Fogel, 2013;Karimi et al, 2018;Moitinho-Silva et al, 2017;Thomas, Rusch, et al, 2010), acclimation to ocean acidification (Ribes et al, 2016), reduction in host surface fouling (On, Lau, & Qian, 2006) and production of compounds that deter predation of the sponge host (Garate, Blanquer, & Uriz, 2015). Sponge-associated microbes are also of significant biotechnological interest due to their potential for production of novel, pharmaceutically active secondary metabolites .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, unbalancing of their microbial symbioses has been considered to trigger extensive mass mortalities of sponges in the Mediterranean (Webster et al, 2008; Cebrian et al, 2011), and Red Sea (Gao et al, 2014). In addition, some purported benefits that sponges may obtain from their associations with microbes have also been proposed such as, antifungal activity, production of bioactive compounds against predation, roles in nitrogen and carbon cycle and vitamin biosynthesis (Schmidt et al, 2000; Freeman and Thacker, 2011; Hentschel et al, 2012; Freeman et al, 2013), but rarely have been experimentally demonstrated (de Voogd et al, 2015; Garate et al, 2015).…”
Section: Introductionmentioning
confidence: 99%